2022
DOI: 10.31234/osf.io/5nw4y
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The complexity of measuring reliability in learning tasks: An illustration using the Alternating Serial Reaction Time task

Abstract: A large portion of research into procedural memory uses sequence learning tasks, and employs between-subjects experimental designs. As such, it is crucial to establish the psychometric properties of the tasks used. In this study, we estimate the internal consistency and split-half reliability of the alternating serial reaction time (ASRT) task, on a large sample of 180 subjects. We also investigate how various pre-processing choices and the length of the task affect reliability. Our results show that the ASRT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…To measure statistical learning, we applied the ASRT task 18 , a commonly used and highly reliable task (e.g. 52 ). In this task, participants saw four empty circles on a white background, horizontally arranged on the screen.…”
Section: Methodsmentioning
confidence: 99%
“…To measure statistical learning, we applied the ASRT task 18 , a commonly used and highly reliable task (e.g. 52 ). In this task, participants saw four empty circles on a white background, horizontally arranged on the screen.…”
Section: Methodsmentioning
confidence: 99%
“…These are exactly the tasks that were shared between studies. Regarding the second study, we have previously shown that longer ASRT tasks lead to more reliable learning scores (Farkas et al, 2022), which are crucial for correlational research designs. Thus, if anything the longer task should increase the power of our replication attempt.…”
Section: Discussionmentioning
confidence: 98%
“…Thirdly, the task consisted of 45 blocks. We previously observed that although acceptable levels of reliability emerge even with 25 blocks, longer tasks lead to more reliable learning scores, which might be crucial for the correlational analyses we planned here (Farkas et al, 2022). Finally, the timing of the stimuli differed.…”
Section: Tasksmentioning
confidence: 90%
“…1 ). During the Learning phase (Day 1), participants performed a widely used and reliable 55 four-choice visuomotor reaction time task called Alternating Serial Reaction Time (ASRT) task 29 , 56 , in which they acquired the associations of Sequence A. This is referred to as old knowledge throughout the paper.…”
Section: Methodsmentioning
confidence: 99%